Performance as a cause of termination of the employment contract - Gorelli Hernández, Juan (2020)
This text deals with the topic of performance as part of the mandatory content of the employment contract. The worker is forced to work with the necessary implication of achieving a certain performance. The quantification of this complicated result therefore raises the possibility of termination of the employment contract as a result of breach of performance due throughout this article.